Desenvolvimento profissional do professor experiente no projeto colaborativo universidade/escolas : desafios e necessidades formativas - Souza, Sueli de Oliveira (2017)
The present research has its origin in the project approved by the Program of Graduate Studies in Education of the Federal University of Mato Grosso/University campus of Rondonópolis (PPGEdu/UFMT/CUR) along with the Observatory of Education/OBEDUC/INEP/ SECADI/2012, which has as focus the beginner teacher and its professional development, difficulties and necessities, and, in this context, offers continuous professional teacher education in the itinerant form to six schools of Basic e Education. The OBEDUC project provides the process of orientation and support to teachers in beginning of the career by means of continuous professional teacher education and the support assisted by an experienced teacher, being this the focus of the present research. The experienced teacher is conceived in this study as that professional who, besides the years of experience, has significant work with his/her peers, who mobilizes knowledge to cope with the situations of practice with more confidence. This research aimed to comprehend how the professional development of the experienced teacher in monitoring the beginner teacher happens in the project PPGEdu/UFMT/OBEDUC, from the continuous professional teacher education requested by them as a form of minimizing their difficulties in the attendance to their educational necessities. It adopts a qualitative approach, with the (auto)biographical method, having as instruments the field diary, educational and learning memorials and interviews of four experienced teacher who disclosed of the investigation. Therefore, the research brought as inquiry: what educational necessities do experienced teachers manifest to be necessary for the performance in the activity of monitoring the beginner teacher? What do these professionals register on their professional development along the Project of continuous professional teacher educational carried out by the PPGEdu/UFMT/OBEDUC for the attendance to their claims? The results point out that the experienced teachers are little assisted by the proposals of teacher education and their involvement in the Project PPGEdu/UFMT/OBEDUC presented traces of professional development signaled by the changes of comprehension regarding the beginner teacher, upon problematizing with the collective of the school the necessity of a distinguished attendance to the new teacher. The results also indicated that the fact that the project brings to the meeting of experienced teacher education their dilemmas and challenges on accompanying the beginner teacher socialized necessities and experiences that broadened the teacher education/development of the participants.